Biochemistry, hormones and adipocytokines in prepubertal children born with IUGR evoke metabolic, hepatic and renal derangements. Issue 1 (December 2018) - Sidiropoulou, Elpida; Paltoglou, George; Valsamakis, George; Margeli, Alexandra; Mantzou, Aimilia; Papassotiriou, Ioannis; Hassiakos, Dimitrios; Iacovidou, Nicoletta; Mastorakos, George
Abstract Children born with IUGR develop features of the metabolic syndrome and exhibit deranged markers of hepatorenal physiology. Metabolic and hepatorenal biochemistry and thers9939609 FTO polymorphism were investigated in prepubertal children born with IUGR. Ninety-eight prepubertal children (46 IUGR and 52 AGA), subdivided in <5 years and >5 years old groups were included. Anthropometry; creatinine, eGFR, urea, AST, ALT, triglycerides, uric acid, total cholesterol, HDL-c, LDL-c, glucose, C-peptide, insulin and glucagon z-scores; HOMA-IR; leptin and adiponectin concentrations;rs9939609 FTO polymorphism frequency were measured. In males, weight and ALT were higher and adiponectin was lower, in IUGR < 5 years; C-peptide, insulin and leptin were higher in IUGR > 5 years; C-peptide was higher in all IUGR, than the respective AGA. In females, creatinine and triglycerides were higher in IUGR < 5 years old; creatinine was higher and eGFR was lower in all IUGR, than the respective AGA. In males and females, creatinine was higher in all IUGR, than the respective AGA; C-peptide, insulin and HOMA-IR were lower, and AST was higher in IUGR < 5 than in IUGR > 5 years old. FTO rs9939609 frequency did not differ between IUGR and AGA. In conclusion prepubertal males born with IUGR increased weight, insulin and leptin and decreased adiponectin, as compared to males born AGA, emerge as early metabolic syndrome characteristics. The concentrations of these hormones do not differ between prepubertal males and females born with IUGR. Weight control, healthy nutrition and physical exercise should be recommended to these children. The deranged renal (particularly evident in females below the age of 5) and liver biochemistry in prepubertal children born with IUGR suggests that hepatorenal derangements might commencein utero . Regular checkup of biochemical and lipid profile is recommended for all children born with IUGR.